Enzyme Polymorphism in Sitophilus oryzae (Linnaeus, 1763) and Sitophilus zeamais (Motschulsky, 1855) (Coleoptera, Curculionidae) in southern Brazil - Danielle das Neves Bespalhok (Acta Scientiarum. Biological Sciences, 2015)
Beetles of the species Sitophilus oryzae and S. zeamais are pests of great economic importance since they attack not only rice and maize but also several other cereals. In fact, these beetles are one of the most visible threats to sustainable food production. Current study estimated the genetic variability of S. oryzae in two samples, one from the State of Paraná (PR), Brazil, and another from the state of Rio Grande do Sul (RS), Brazil, and a sample of S. zeamais from the State of Santa Catarina (SC), Brazil. Isozyme electrophoresis in starch gel technique was employed to analyze eight enzyme systems (AAT, ACP, GDH, GPI, IDH, MDH, PGM and ME). Average heterozygosity rates were 0.0091, 0.0100 and 0.0000 and expected heterozygosity rates were 0.0419, 0.0452 and 0.0000 respectively for the samples of PR, SC and RS samples. The percentage of polymorphic loci was 30% in the PR sample, 0% in the RS sample and 30% in the SC sample. Genetic identity rates were I=0.9983 between samples from PR and RS; I = 0.6892 between PR and SC, and I = 0.6925 between SC and RS. Nei ́s (1978) genetic distance rates were 0.0017, 0.3722 and 0.3675. Samples presented low genetic variability.